Modeling Atmosphere-Ocean Radiative Transfer: A PACE Mission Perspective - Chowdhary, Jacek; Zhai, Peng-Wang; Boss, Emmanuel; Dierssen, Heidi; Frouin, Robert; Ibrahim, Amir; Lee, Zhongping; Remer, Lorraine A.; Twardowski, Michael; Xu, Feng; Zhang, Xiaodong; Ottaviani, Matteo; et al. (Frontiers in Earth Science, 2019)
This report summarizes the research frontiers on radiative transfer (RT) in coupled atmosphere-atmosphere systems to enable new science and specifically to support simulations and interpretations of remote sensing observations from the upcoming Plankton, Aerosol, Cloud ocean Ecosystem (PACE) mission. Given that (i) there is a multitude of atmospheric and oceanic constituents at any given moment that each exhibit a large variety of physical and chemical properties and that (ii) light-matter interaction can occur in various ways (scattering, absorption, and emission), it becomes clear that it is impossible to tackle all outstanding RT aspects related to interpreting and/or simulating light reflected by atmosphere-ocean systems. Instead, we performed both theoretical and experimental studies on a discrete set of RT topics that are of importance to (a) the science threshold and goal questions of the PACE mission and (b) the measurement capabilities of the instruments currently envisioned for this mission. These topics cover (1) the ocean (i.e., water body): exact (elastic and inelastic scattering) and approximate (bio-optical) forward RT models used for scattering and absorption by pure water and particulates, (2) the air-water interface: extracting and/or accounting for variations in surface refractive index and whitecaps and underwater bubbles in actual imagery, (3) the atmosphere: aerosol and gas RT models for polarimetric and/or hyperspectral remote sensing, and (4) atmosphere-ocean systems: RT benchmark results for horizontally homogeneous plane-parallel systems, and impact of the Earth’s sphericity and adjacency effects on RT analyses of space-borne observations. We provide for each topic a summary of past relevant (heritage) work, followed by a discussion (for unresolved questions) and RT updates.